2008
DOI: 10.1161/hypertensionaha.107.105239
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Activity as a Target of Hormone Replacement Therapy–Dependent Plaque Stabilization in Postmenopausal Women

Abstract: Abstract-The molecular mechanisms of the atheroprotective effect evoked by hormone replacement therapy in postmenopausal women is not well known. Recently, we have demonstrated enhanced activity of the ubiquitinproteasome system in human atherosclerotic plaques and evidenced that it is associated with inflammatory-induced plaque rupture. Therefore, we hypothesized that hormone replacement therapy may exert the cardioprotective effects modulating the ubiquitin-proteasome activity. To investigate this possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Plaques from patients with morning surges in blood pressure have increased protein ubiquitination and 20S proteasome activity which is associated with increases in NF-kB, TNFa, inflammatory cell number, markers of oxidative stress, and matrix metalloproteinase 9, but decreases in collagen content and IkB levels compared to controls43. Similar findings have been reported in plaques from post-menopausal women not receiving hormone replacement therapy compared to those who are 44, and in plaques from diabetics not treated with rosiglitazone compared to those who were treated42. These findings demonstrate that protein ubiquitination and 20S proteasome activity is associated with inflammation, oxidative stress, and histologic changes leading to an unstable plaque phenotype.…”
Section: The Role Of the Ups In The Pathophysiology Of Atherosclerosissupporting
confidence: 63%
See 2 more Smart Citations
“…Plaques from patients with morning surges in blood pressure have increased protein ubiquitination and 20S proteasome activity which is associated with increases in NF-kB, TNFa, inflammatory cell number, markers of oxidative stress, and matrix metalloproteinase 9, but decreases in collagen content and IkB levels compared to controls43. Similar findings have been reported in plaques from post-menopausal women not receiving hormone replacement therapy compared to those who are 44, and in plaques from diabetics not treated with rosiglitazone compared to those who were treated42. These findings demonstrate that protein ubiquitination and 20S proteasome activity is associated with inflammation, oxidative stress, and histologic changes leading to an unstable plaque phenotype.…”
Section: The Role Of the Ups In The Pathophysiology Of Atherosclerosissupporting
confidence: 63%
“…TNFa stimulates inflammation and immune responses in part through activation of NF-kB, a nuclear transcription factor that plays an important and central role in the generation of inflammation, apoptosis and cell proliferation. In carotid artery plaques from patients with various clinical characteristics, protein ubiquitination and 20S proteasome activity is correlated with the presence of TNFa and NF-kB 4244. Plaques from patients with morning surges in blood pressure have increased protein ubiquitination and 20S proteasome activity which is associated with increases in NF-kB, TNFa, inflammatory cell number, markers of oxidative stress, and matrix metalloproteinase 9, but decreases in collagen content and IkB levels compared to controls43.…”
Section: The Role Of the Ups In The Pathophysiology Of Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized, controlled study46 revealed that plaques from diabetic patients contain more ubiquitin, proteasome activity, and markers of oxidative stress (3-nitrotyrosine and O 2 •− production) than those of control patients. Recently, the atheroprotective effects of hormone replacement therapy in postmenopausal women were linked to inhibition of the ubiquitin-proteasome system through decreased oxidative stress 47. The present findings suggest that this clinically observed upregulation of the ubiquitin-proteasome system by oxidative stress results, at least in part, from a disease-associated modification of PA700, likely through ONOO − -dependent tyrosine nitration.…”
Section: Discussionsupporting
confidence: 51%
“…. More recently, a study has been published supporting the hypothesis that HRT inhibits plaque ubiquitin-proteasome activity by decreasing oxidative stress generation in postmenopausal women [19].…”
Section: Discussionmentioning
confidence: 97%